Cover Picture: Soft Alloys Constructed with Distinct Mesoatoms via Self‐Sorting Assembly of Giant Shape Amphiphiles (Angew. Chem. Int. Ed. 19/2022). Issue 19 (31st March 2022) - Wang, Yicong; Huang, Jiahao; Yan, Xiao‐Yun; Lei, Huanyu; Liu, Xian‐You; Guo, Qing‐Yun; Liu, Yuchu; Liu, Tong; Huang, Mingjun; Bian, Fenggang; Su, Zebin; Cheng, Stephen Z. D.
Abstract : Metal alloy superlattices with large volume asymmetry were constructed based on self‐sorting assembly of binary giant shape amphiphiles, as reported by Zebin Su, Stephen Z. D. Cheng et al. in their Research Article (e202200637) . MgZn2, NaZn13, and CaCu5 superlattices were observed in soft matters, and the thermodynamic origin of their formation was quantitatively analyzed.